2017
DOI: 10.2514/1.c033995
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of Severity and Mitigation of Wake-Vortex Encounters in Ground Proximity

Abstract: Wake-vortex encounter reports as well as simulations show a significantly higher encounter probability during landing shortly before touchdown in comparison to other flight phases. This is caused, among other factors, by the special behavior of wake vortices in ground effect. Nevertheless, hazardous wake encounters with adverse consequences are rarely reported in reality. To gain more insight in the mechanisms of wake encounters close to ground, encounter simulations were performed with realistic vortex flowfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…where lnk τ is the initial connection time of the wake vortex. The motion of the wake vortex accelerates after the formation of the irregular vortex ring, and this phase is primarily governed by long-term spontaneous diffusion induced by turbulence [30]. The lateral distance of the wake vortex with time is where bias t is the bias time and represents the moment when the longwave instability reaches the point of maximum amplitude.…”
Section: Hazard Zone Movements Due To Wind and Ground Effectsmentioning
confidence: 99%
“…where lnk τ is the initial connection time of the wake vortex. The motion of the wake vortex accelerates after the formation of the irregular vortex ring, and this phase is primarily governed by long-term spontaneous diffusion induced by turbulence [30]. The lateral distance of the wake vortex with time is where bias t is the bias time and represents the moment when the longwave instability reaches the point of maximum amplitude.…”
Section: Hazard Zone Movements Due To Wind and Ground Effectsmentioning
confidence: 99%
“…The vortex Reynolds number defined in terms of circulation strength, Γ, and kinematic viscosity, ν, proves suitable for capturing this type physics [21]. The literature has reported that physics associated with the rebounding effect does not occur unless the viscous boundary layer condition is imposed on the runway [22][23][24][25][26]. Figure 8 shows the phenomena above interpreted including a crosswind velocity of magnitude U = 0.04 blowing the primary vortical structures.…”
Section: Aircraft Wake Vortices In Ground Effect With Crosswindmentioning
confidence: 99%
“…The problem of the dissipation of aircraft vortex wakes has been the focus of extensive studies aiming to predict the potential hazard of wake vortices and their lifetime in the ground effect [22][23][24][25][26]. The air always flows from a region of high pressure to a region of low pressure, and in the case of the aircraft wing, air flows from below the wing to the upper surface of the wing.…”
Section: Introductionmentioning
confidence: 99%
“…Lidar measurements at Vienna airport showed that a Plate Line is able to effectively reduce the wake vortex lifetime [8], especially of the longest-living vortices. Also, a ight simulator study revealed that the faster decayed vortices reduce the severity of a wake encounter and increase the pilot acceptance of such disturbances [9]. Hence, the previous investigations showed the effectiveness of the plates to lower the risk of hazardous wake encounters in ground proximity and thus increase ight safety.…”
Section: Introductionmentioning
confidence: 96%